Inherently loyal or easily bored?: Nonconscious activation of consistency versus variety‐seeking behavior - Fishbach, Ayelet; Ratner, Rebecca K.; Zhang, Ying (Journal of Consumer Psychology, 2011)
AbstractThis article explores nonconscious effects on consumers' tendency to seek consistency versus variety in sequential choices. We propose that activation of concepts related to a positive frame of repetition (e.g., “loyalty”) triggers a preference‐based construal of consumption that encourages consistency seeking. In contrast, activation of concepts related to a negative frame of repetition (e.g., “boredom”) triggers a satiation‐based construal of consumption that encourages variety seeking. Four studies demonstrate that which construal of consumption consumers adopt can be activated outside of awareness, impacts consumers' experienced satiation, and determines in turn the amount of variety they incorporate into their choices.